Integral Treatment of the Diabetes Mellitus from an Educative Standpoint - Elodia Rivas Alpizar; Caridad Hernández Gutiérrez; Grethel Quintana Beyra; Belkys Clavero Ramírez; Gisela Zerquera Trujillo (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2007)
The document presented constitutes an educative material for diabetic patient´s education in health institutions in our country. It was elaborated due to the neccessity of a methodological tool which includes updated contents about this disease. It can be used as a guide for the health personnel (physicians, and paramedics) who are directly involved in the development of actions of an integral educative work in the treatment of patients suffering form diabetes mellitus. It also can be used for the educative work about non transmissible chronic diseases.